2020
DOI: 10.1155/2020/2684672
|View full text |Cite|
|
Sign up to set email alerts
|

Phillyrin Mitigates Apoptosis and Oxidative Stress in Hydrogen Peroxide-Treated RPE Cells through Activation of the Nrf2 Signaling Pathway

Abstract: Oxidative stress-induced dysfunction or apoptosis in retinal pigment epithelial (RPE) cells is an important cause of dry age-related macular degeneration (AMD). Although phillyrin has been shown to exert significant antioxidant effects, the underlying mechanism of action remains unclear. The purpose of this study was to investigate the protective effect of phillyrin on hydrogen peroxide- (H2O2-) induced oxidative stress damage in RPE cells and the potential mechanism involved. It was found that phillyrin signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 58 publications
1
22
0
Order By: Relevance
“…A mitochondria protein of the cellular outer membrane in the mitochondria of several cells, including ARPE19 is TSPO. Accumulating evince indicates that the presence of TSPO participated the modulations of Ca 2+ homeostasis and mitochondrial fROS generation [10,11]. The deletion of TSPO gene provides to study the action of TSPO on the levels of apoptosis, ADPR, Mito-fROS and apoptosis via the stimulation of Ca 2+ permeable channels in the models of cell culture [40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A mitochondria protein of the cellular outer membrane in the mitochondria of several cells, including ARPE19 is TSPO. Accumulating evince indicates that the presence of TSPO participated the modulations of Ca 2+ homeostasis and mitochondrial fROS generation [10,11]. The deletion of TSPO gene provides to study the action of TSPO on the levels of apoptosis, ADPR, Mito-fROS and apoptosis via the stimulation of Ca 2+ permeable channels in the models of cell culture [40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…The dry AMD isn’t totally treated by the current drugs. However, accumulation data indicate that inhibition of excessive fROS generation in the membranes of retinal mitochondria is a reasonable way for the treatment of dry AMD disease [ 1 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Under physiological conditions, Keap1 combines with and inhibits Nrf2. Under the in uence of external oxidative stressors, Nrf2 is decoupled with Keap1 and combined with the antioxidant response element ARE to activate the Nrf2 signaling pathway, thereby increasing the expression of antioxidant proteins HO-1, SOD, NQO1, etc., and reducing oxidative damage and accumulation of toxicity metabolites [49,50] . In a study by Wang et al…”
Section: Discussionmentioning
confidence: 99%
“…When the occurrence of oxidative stress, Nrf2 phosphorylation, and Keap1 protein translocation into the uncoupling combine with ARE in the nucleus, regulation on downstream target genes, such as Heme Oxygenase-1 (HO-1) and NAD(P)H quinone dehydrogenase 1 (NQO1), is induced, to enhance the process of detoxi cation and antioxidant ability of cells [29][30][31]. In vitro experiments have also shown that the upregulation of HO-1 and NQO1 can protect cells against oxidative damage of glutamic acid, hydrogen peroxide, and amyloid beta-protein [32][33][34].…”
Section: Discussionmentioning
confidence: 99%